Teknik Pengawetan Basah Ramah Lingkungan untuk Spesimen Invertebrata Laut dan Alga - Nurwendah, Anisa Solehah; Jayanto, Pery; Putri, Meirin Dwiningtyas; Harahap, Sahrona; Hilmi, Yugi; Nihlatuljannah, Halwa; Julianti, Amelia Rizkia; Ripal, Ripal (Universitas Pahlawan Tuanku Tambusai, 2025)
Biological specimen preservation techniques have an important role in supporting educational, research and conservation activities. However, conventional methods using harmful chemicals like formalin pose risks to health and the environment. This community service activity aimed to introduce environmentally friendly wet preservation techniques for marine invertebrates and algae as safer alternatives. The program consisted of three sessions: theoretical training, practical demonstrations, and fieldwork in coastal areas. A total of 47 biology education students (class of 2023) participated, successfully collecting and preserving 15 specimens using eco-friendly materials such as 70% ethanol and glycerin. Evaluation showed the preserved specimens maintained good quality and were suitable as biology learning media. Additionally, the activity increased participants’ awareness of marine biodiversity conservation and provided tangible support for sustainable, eco-conscious biology education.